The Double-Edged Sword of SIRT3 in Cancer and Its Therapeutic Applications - Ouyang, Shumin; Zhang, Qiyi; Lou, Linlin; Zhu, Kai; Li, Zeyu; Liu, Peiqing; Zhang, Xiaolei (Frontiers in Pharmacology, 2022)
Reprogramming of cellular energy metabolism is considered an emerging feature of cancer. Mitochondrial metabolism plays a crucial role in cancer cell proliferation, survival, and metastasis. As a major mitochondrial NAD+-dependent deacetylase, sirtuin3 (SIRT3) deacetylates and regulates the enzymes involved in regulating mitochondrial energy metabolism, including fatty acid oxidation, the Krebs cycle, and the respiratory chain to maintain metabolic homeostasis. In this article, we review the multiple roles of SIRT3 in various cancers, and systematically summarize the recent advances in the discovery of its activators and inhibitors. The roles of SIRT3 vary in different cancers and have cell- and tumor-type specificity. SIRT3 plays a unique function by mediating interactions between mitochondria and intracellular signaling. The critical functions of SIRT3 have renewed interest in the development of small molecule modulators that regulate its activity. Delineation of the underlying mechanism of SIRT3 as a critical regulator of cell metabolism and further characterization of the mitochondrial substrates of SIRT3 will deepen our understanding of the role of SIRT3 in tumorigenesis and progression and may provide novel therapeutic strategies for cancer targeting SIRT3.